The prevalence of TMJ dysfunction in a partially dentulous population - Dimayuga, Ma. Regina G.; Sevilla, Ma. Fatima SA.; Ladao Jr., Joaquin (Adviser).
Questionnaires and clinical examinations were used to establish the prevalence of TMJ dysfunction syndrome in the randomly sampled (118 dentulous individuals from the student population of the U.P. College of Dentistry. Analysis of data revealed that 85.59% of the individuals exhibited the dysfunction. Frequencies of the clinical signs and symptoms were likewise drawn from the investigations joint noise, gnashing/grinding of teeth, and frequently occurring headaches were the most common symptoms experienced by the afflicted individuals while TMJ sounds, deviation of the mandible during movement, and facial asymmetry were the common clinical signs manifested. It was found that the percentage of the afflicted individuals aware of the TMJD symptoms was relatively high.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Temporomandibular joint -- Diseases; Occlusion (Dentistry).